KETERLIBATAN EGO TERHADAP KEPERCAYAAN DAN KOMITMEN DALAM MENINGKATKAN MINAT ANGGOTA (Studi Pada KSPPS BMT Nusantara Mojopahit Mojokerto) - Badriyah, Mufasikhatur Robiatul; Indra Lesmana, Ceta (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2024)
This research aims to analyze how ego involvement increases the interest of members or customers at KSPPS BMT Nusantara Mojopahit Mojokerto. As an effort to change the negative perspective that appears in society. This research uses a qualitative approach with descriptive research type. Data collection techniques were carried out using interview, observation and documentation techniques. The data analysis technique uses descriptive analysis with stages of data reduction, data presentation, and drawing conclusions. The research results show that ego involvement carried out by KSPPS BMT Nusantara Mojopahit through product variations, good service quality and in accordance with members' needs and desires plays a role in overcoming the impact of negative views in society. Suitable product variations and affordable margins increase public interest in KSPPS BMT Nusantara Mojopahit. The quality of service maintained by BMT Nusantara Mojopahit creates a positive experience for members and overcomes the community's negative views of cooperatives. Ego involvement built through personal communication, shared identity (NU) with the community, and word of mouth marketing (WOM) succeeded in attracting greater public interest in KSPPS BMT Nusantara Mojopahit.